Social Enactivism: On Situating High-Level Cognitive States and Processes - Mark-Oliver Casper
Social enactivism is a philosophical theory which, through the analysis of discursive practice, aims at explaining how high-level cognitive conditions and processes emerge. The fundamental tenets of this theory are based on enactivist and (neo)pragmatist principles. Therefore, the emphasis is not on the purely linguistic understanding of discourse but on its structural interaction with technology, that is created by man himself, in the context of which the discursive performance takes place. This perspective addresses not only a blind spot in the international debate about "situated cognition" but also a current problem in the philosophy of mind.